2010
DOI: 10.1519/jsc.0b013e3181d32e29
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Exertion in Different Strength Exercise Loads in Sedentary, Active, and Trained Adults

Abstract: The aim was to analyze the relationship between the perceived exertion (PE) and different loads in strength exercises (SEs), in sedentary, active, and trained adult subjects. Thirty young men (18-34 years) were divided into 3 groups (experimental group [EG]): sedentary EG (SEG), physically active group (PAG), and the strength trained group (STG). Maximum strength was established using the 1 repetition maximum test (1RM). Using series of 12 repetitions, different loads were applied until the 4 ratings of PE (RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 14 publications
6
51
0
4
Order By: Relevance
“…In other words, the closer a person gets to doing maximum repetitions, the easier it is to estimate the TZ. Others have also shown that it is easier to perceive effort at the highest intensities (Day et al, 2004;Suminski et al, 1997;Tiggemann et al, 2010). Together, these results support the complexity behind the neurophysiological pathways concerning perception of effort.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In other words, the closer a person gets to doing maximum repetitions, the easier it is to estimate the TZ. Others have also shown that it is easier to perceive effort at the highest intensities (Day et al, 2004;Suminski et al, 1997;Tiggemann et al, 2010). Together, these results support the complexity behind the neurophysiological pathways concerning perception of effort.…”
Section: Discussionsupporting
confidence: 71%
“…Such empirical comprehension makes sense because maximum number of repetitions are associated with perceived effort. Indeed, as mentioned before, there is a linear or quadratic relationship between intensity and perception of effort (Suminski et al, 1997;Tiggemann et al, 2010). Furthermore, it has been shown that is possible to feel the effort during the first repetitions (Pincivero et al, 2003).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…When examined with reference to increasing load prior work is contrasting as to whether differences in RPE exist between trained and untrained persons. 42,43 However, again it seems that any difference that might exist becomes less meaningful as trainees approach MF 18 . This suggests that the scales examined here might be suitable for use in young and old, male and female, and trained and untrained populations, when RT is performed near to or at MF.…”
Section: Figure 3 Scatter Plot Of Rpe-e and Rpe-d For Combined Datamentioning
confidence: 99%
“…Physicians, physical therapists, and medical staff should use RPE for determining the intensity of resistance exercise in clinical practise. [22][23][24][25][26][27][28][29]. The rating on the Borg 15-point RPE scale increased as the intensity of resistance exercise increased.…”
Section: Introductionmentioning
confidence: 99%